Exploring the experiences of queer international students accessing mental health support in Victoria, Australia - Hu, Xin; Flynn, Catherine (Journal of International Students, 2024)
International students (IS) generate significant revenue in Australia, bringing diversity, but also distinctive needs and values. IS experience unique mental health challenges and their unmet support needs have recently received public and academic attention, notably during the COVID-19 pandemic. A small number of existing Australian studies have examined IS mental health experiences, focusing on their individual behaviours and attitudes towards help seeking. However, framing IS as homogeneous misses important variations within this population. This study therefore explores the experiences of a diverse IS subgroup - queer international students (QIS), and the barriers and facilitators that influence how they seek and gain mental health support. Semi-structured interviews were conducted with six QIS studying in Victoria. Results show that the persistent impacts of broader socio-cultural factors and systemic gaps act as barriers for QIS to access support, while awareness of intersectionality is critical in providing appropriate professional assistance to QIS.